Cryptocurrency regulation: tendencies and challenges in the European Union - Ziemele, Sanda (Riga Graduate School of Law, 2018)
While the popularity of cryptocurrencies is growing, the regulation of cryptocurrencies still remains largely underdeveloped body of law. In order to understand the ongoing debate of cryptocurrency regulation, it is crucial to understand the mechanics of cryptocurrency. Therefore, the research has described the decentralized nature of cryptocurrencies, regarding them as a form of ‘electronic cash’ that lacks the backing of a government authority and relies on cryptography to control its creation, circulation and verification.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Cryptocurrencies